A device to measure joint angles and foot force for lower extremity force distribution computations - (:unkn) unknown (IEEE Computer Society, 2013)
In rehabilitation of walking difficulties, it is vital to be aware of the distribution of the force and moment pairs faced by the lower limb extremities. The mathematical equations for numerical computation of these pairs are provided by free body diagrams that require some foot force measurements and joint/segment-tilt angle measurements as well. In this study, a device has been developed to capture the foot force and the ankle, knee and hip joint angles. The device is equipped with three accelerometers and six force sensitive resistors. The measured forces and angles are computed and next transferred to personal computer. The device is calibrated and then tested on a healthy volunteer. The test results show that the device may be used to provide valuable measurements to compute force distributions in lower extremity. © 2013 The Chamber of Turkish Electrical Engineers-Bursa.